Researching and Transforming Adult Learning and Communities: The Local/Global Context - Beneficiary, ESREA; Evans, Rob; Kurantowicz, Ewa; Lucio-Villegas, Emilio (Research on the education and learning of adults, 2016)
FREELY AVAILABLE ONLINE AS OPEN ACCESS BOOK! Can adult education and learning be understood without reference to community and people's daily lives? The response to be found in the chapters of this volume say emphatically no, they cannot. Adult learning can be best understood if we look at the social life of people in communities, and this book is an attempt to recover this view. The chapters of this volume reflect ongoing research in the field of adult education and learning in and with communities. At the same time the work of the authors presented here offers a very vital reflection of the work of the ESREA research network Between Local and Global--Adult Learning and Communities. The chapters showcase the broad range of professional practice, the variety in both methodology and theoretical background, as well as the impressive scope of field research experience the authors bring to bear in their papers. The first section provides the broad view of research into adult learning and community development emphasising how social movements are at the heart of local and global change and that they are critically important sources of power. The second section focuses in on the practice of educators/mediators working in local and regional contexts in which the tensions of the wider policy and discourse environment impact on adult learners. The third section privileges the view at the close level of research inside local communities in the field. International researchers and practitioners, particularly young researchers, who are active in adult learning and in local/global communities will be interested in this book. The emphasis of the chapters is on participatory and emancipatory social research. Empowerment of women in rural communities, involvement of communities in social and environmental movements, power-sharing in community research projects and the exposure of hegemonic, globalising forces at work in ethnic communities are among the themes developed in this volume.